Management of Patients with Urinary Stone Obstruction a Single-Center Study - Kifayat Tariq, Samiullah Opal, Sikandar Hayat, Ihsanullah Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: This study aims to characterize the clinical manifestations, location of the obstruction, and surgical intervention results of individuals with obstructive urethral stones. Study design: A single-center study Place and Duration: IKD Peshawar, Departboyst of Urology, from January 1, 2020, to January 1, 2021. Methods: 124 obstructive urethral stones were treated at IKD Peshawar. 4 to 14-year-old patients Obstructive urethral stones were treated surgically by removing the stone from the external urethral meatus (stone retrieval) with or without Meatotomy, retrograde manipulation (push back), and then cystolithoclasty or cystolitholapaxy, depending on the stone’s position and size. Results: The mean age was 04±12.14 was between 10 and 12 years old. A total of 118 boys (98%), together with 06 girls (02%), were aged 13 and above. Sixty boys had stones in the proximal urethra (prostatic and membranous) or bulbar urethra, while 24 boys had stones in the external urethral meatus. Stones were found in the external urethral meatus of 60 boys individuals. Conclusion: For the most part, obstructive urethral stones may be managed with endoscopic therapy, but in certain situations, a minor operation like a meatotomy is necessary. Keywords: urethral obstruction, managment t, outcome, surgery, intervention